Permanent and sporadic loss of the semivowel [w] after consonants in medieval English, with special reference to so, also and such - Wełna, Jerzy (Adam Mickiewicz University, 2006)
The deletion of the semivowel [w] adjacent to other consonants, especially [s], was a process initiated in Early Middle English, a period which saw the reduction of the semivowel in adverbs like also (OE ealswa), so (OE swa) and the pronoun such (OE swylc), all exhibiting very high frequency of occurrence. In the present study attention is focussed on the three items, whose contemporary spellings demonstrate the deletion of [w], which occurred much earlier than the traditional grammars say. These three must have been affected by the loss in the order (1) swa, (2) ealswa, (3) swylc, in a process which followed the natural path of lexical diffusion. Because all the three words have always shown a high degree of grammaticalisation, the latter may be held responsible for the relevant loss of their substance.